Interferon-gamma: A Potent Antiviral Agent Targeting Macrophages Infected with LP-BM5 Murine Leukemia Virus, the Causative Agent of 'AIDS' in Mice - Jens J Kort; Julie L Eiseman (Canadian Journal of Infectious Diseases)
Cells of the monocyte/macrophage lineage (MM cells) are known to be infected by retroviruses, including the human immunodeficiency virus (HIV), without cytopathic changes and may serve as a persistent reservoir for the virus during the development of immunodeficiency disease. LP-BM5 murine leukemia virus (MuLV) infection of C57BL/6 mice and cell lines has been used to optimize therapy directed against macrophages. Findings in this murine system may be applicable to HN infection in humans. The effect of recombinant murine interferon-gamma (IFN-γ) and 3' -azido-2',3' -dideoxythymidine (AZT) as single agents or in combination was investigated in both LP-BM5 MuLV de novo infection and chronic infection of macrophages. Results indicate that the therapeutic effects of these single agents were dose-dependent and both agents were similarly effective in reducing the production of infectious virus determined by XC-plaque assay and by measurements of reverse transcriptase activity in culture supernatants; and AZT and IFN-γ reduced the production of virus proteins, quantified by laser densitometry of fluorographs from immunoprecipitated viral proteins using virus-specific antiserum. A combination of IFN-γ and that AZT showed greater antiviral activity in both LP-BM5 MuLV de novo and chronic infection of macrophages than either agent alone, suggesting that IFN-γ and AZT represent a potent combination of antiviral agents targeting macrophages. Further, since a lower concentration of each agent was required for efficacy in combination therapy, toxicity associated with single agent therapy may be avoided.